IN VITRO ANTIOXIDANT ACTIVITY AND WOUND HEALING ACTIVITY OF WHEATGRASS BY 1,1- DIPHENYL, 2 PICRYLHYDRAZYL METHOD - Alekhya, Veermaneni; Deepan, Thiyagarajan; Dasaratha Dhanaraju, Magharla (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to evaluate in vitro antioxidant activity and wound healing activity in Triticum aestivum (wheat grass). Methods: T. aestivum commonly known as Wheatgrass had a wide range of health benefits among the young grass of common wheat plant components includes chlorophyll, flavonoids, and Vitamins A, C, and E. Wheatgrass is used in Folklore medicine for treatment of skin diseases and wound healing. In our present study, petroleum ether, ethanol and aqueous extracts of T. aestivum have been evaluated for in vitro antioxidant activity and wound healing activity by 1,1- diphenyl, 2 Picrylhydrazyl radical scavenging activity, and Chick chorioallantoic method, respectively. Results: The results of both the assay showed that all the extracts of T. aestivum have significant antioxidant and wound healing activity on dose-dependent manner. Conclusion: The wheatgrass has antioxidant and wound healing activity.